The influence of CD 4+t cells, hiv disease stage and zidovudine on hiv isolation in Bahia, Brazil - Brites,Carlos (1996)
HIV-l isolation was attempted on 72 individuais, including persons with knoum HIV infection and five without proven HIV infection but with indeterminate Western blot patterns, as well as on low-risk HIV seronegative persons. The ahility to detect HIV- 1 frorn culture supernatant by p24 antigen capture assay was evaluated by segregating patients by absolute CD4+ cell counts, clinicai stage of disease, p24 antigenemia and zidovudine use. The likelihood of a p24 positive HIV culture was highest among patients with CD4+ T-cell counts below 200/ul and patients with advanced clinical disease. Use of zidovudine did not affect the rate ofHIV positwity in cultures.